The Urgency of Environmental Accounting as a Business Sustainability Strategy (Case Study of PT. Gonusa Prima Distribusi): Akuntansi lingkungan,keberlanjutan bisnis - Djudahril, Fakhri; Mas'ud, Masdar; Tenriwaru, Tenriwaru (Economos : Jurnal Ekonomi dan Bisnis, 2024)
ABSTRACT Environmental accounting encompasses the management of environmental costs, such as pollution control, waste disposal, natural resource maintenance, and the implementation of environmentally friendly practices within business operations. This study aims to assess the extent to which environmental accounting can serve as a benchmark for business sustainability at PT. Gonusa Prima Distribusi. This research is classified as qualitative with a case study approach. In this study, there are 8 informants. Data collection techniques include observation, interviews, and documentation. The researcher conducted a direct visit to the research site, PT. Gonusa Prima Distribusi, located at Pergudangan Parangloe Indah, Blok Hall 5 No. 6, Kelurahan Parangloe, Kecamatan Tamalanrea, Makassar City, South Sulawesi Province. The methods used include interviews, observation, and documentation. The results of the study indicate that the implementation of environmental accounting at PT. Gonusa Prima Distribusi is quite effective, allowing the company to apply a reasonably good business sustainability strategy. This effective business sustainability strategy also automatically enhances the profitability of PT. Gonusa Prima Distribusi.